Photosynthesis in extreme environments: responses to different light regimes in the Antarctic alga Koliella antarctica - LA ROCCA, NICOLETTA; SCIUTO, KATIA; Andrea Meneghesso; MORO, ISABELLA; Nicoletta Rascio; MOROSINOTTO, TOMAS (Physiologia Plantarum, 2015)
Antarctic algae play a fundamental role in polar ecosystem thanks to their ability to grow in an extreme environment characterized by low temperatures and variable illumination. Here, for prolonged periods, irradiation is extremely low and algae must be able to harvest light as efficiently as possible. On the other side, at low temperatures even dim irradiances can saturate photosynthesis and drive to the formation of reactive oxygen species. Colonization of this extreme environment necessarily required the optimization of photosynthesis regulation mechanisms by algal organisms. In order to investigate these adaptations we analyzed the time course of physiological and morphological responses to different irradiances in Koliella antarctica, a green microalga isolated from Ross Sea (Antarctica). Koliella antarctica not only modulates cell morphology and composition of its photosynthetic apparatus on a long-term acclimation, but also shows the ability of a very fast response to light fluctuations. Koliella antarctica controls the activity of two xanthophyll cycles. The first, involving lutein epoxide and lutein, may be important for the growth under very low irradiances. The second, involving conversion of violaxanthin to antheraxanthin and zeaxanthin, is relevant to induce a fast and particularly strong non-photochemical quenching,when the alga is exposed to higher light intensities. Globally K. antarctica thus shows the ability to activate a palette of responses of the photosynthetic apparatus optimized for survival in its natural extreme environment.